Elderly individuals exhibit dysregulated monocyte responses to viral immune complexes compared to adults and children - Léa Domitien Payet; Anthony Coléon; Anne Sophie Bedin; Lucas Auguste; Maël Morvan Duroyon; Caroline Mollevi; Hubert Blain; Franck Mennechet; Éric Jeziorski; Édouard Tuaillon (Scientific Reports)
Abstract The severity of certain viral infectious diseases varies across the age; we hypothesize that these variations could be related to the variation of immune responses to viral immune complexes (ICs) among the age. This study aimed to investigate monocyte activation in response to ICs in children, adults, and elderly individuals. An experimental in vitro model was established using peripheral blood mononuclear cells from healthy individuals. Monocyte activation markers (CD169, CD38, HLA-DR), the negative co-stimulatory molecule (PD-L1), and cytokine production were measured under basal conditions and upon stimulation with human adenovirus 5-IgG immune complex (Ad5-ICs), interferon-alpha (IFN-α), and lipopolysaccharide (LPS). Monocytes from children and adults displayed similar activation profiles in response to ICs and IFN-α stimulation, characterized by increased expression of CD169 and PD-L1. In contrast, monocytes from elderly individuals exhibited weak or no overexpression of CD169 and PD-L1 coupled with a diminished PBMC cytokine response. Notably, cells from elderly participants produced high levels of TNF-α, IL-1α, and IL-6 in the absence of stimulation. Multiple comparisons confirmed reduced monocyte activation and PBMC cytokine responses in the elderly compared to adults and children. Although children exhibited a significant response to ICs, their secretion of IFN-α, IP-10, IFN-γ, IL-8, and IL-2 was lower than that observed in adults. Our findings suggest that elderly individuals have poor and dysregulated responses to ICs, likely due to immunosenescence and chronic inflammation. Adults exhibit a robust and balanced response to ICs, while children display a moderate response, possibly influenced by ‘trained immunity’ resulting from frequent early-life exposures to pathogens. These insights highlight the importance of further research to develop age-specific therapeutic strategies to modulate immune function during viral IC exposure.